Integrating social support into interventions among the elderly in nursing homes: a scoping review - Daniel Behrendt; Vanessa Wendschuh; Chommanard Sumngern; Sybille Spieker (BMJ Open, 2023)
Objectives This study aimed to understand the evidence related to integration of social support into interventions, to identify literature gaps related to social support interventions, and to clarify dimensions of supportive functions, outcomes, and providers among the elderly in nursing homes.Design This scoping review followed the approach by Arksey and O’Malley. The Mixed Methods Appraisal Tool V.2018 was used for quality assessment of the studies.Data sources Searches were conducted of the PubMed, ScienceDirect, Public Library of Science, SocioHub, Wiley Online Library and PsycINFO databases for publications from 2010 to 2021.Eligibility criteria for selecting studies We searched for primary studies and heterogeneous study designs published in English. Eligible studies took place in nursing and care homes and had study populations of elderly adults (older adults, geriatrics, ageing, seniors, older people and those aged 60 years and older).Data extraction and synthesis A data extraction form based on Joanna Briggs Institute’s recommendations for scoping reviews was used. Two reviewers independently extracted data and performed quality assessment of the studies. Then, extracted data and quality assessment reports were discussed by all authors.Results Thirty-one eligible studies were included in this review. 54.8% of the studies provided interventions for cognitively impaired residents. The top-three outcomes were neuropsychiatric symptoms, physical function and quality of life, respectively. The interventions were performed by nursing home staff (83.9%), other persons with specific qualifications (58.1%) and health volunteers (6.5%). Most studies (90.3%) depicted the integration of emotional and instrumental supportive functions into interventions.Conclusion The appropriate dimensions of supportive function, mainly emotional and instrumental support, are important to integrate into the social care of elderly people living in nursing homes.